Upaya Meningkatkan Kemampuan Anak Belajar Berhitung Permulaan melalui Media Kantong Stik di Tk Bhakti Masyarakat Pagerharjo Pati - Sumiyati, Sumiyati; Daryati, Daryati (Indonesian Journal of Islamic Early Childhood Education, 2017)
The objectives of this research are: (1) To know the ability of early counting learning in the group B at TK Bhakti Pagerharjo Pati, and (2) To know whether the use of pocket sticks media can improve the l ability of early counting in group B at TK Bhakti Masyarakat Pagerharjo Wedarijaksa Pati. This type of research is Clasroom Action Reseach using two cycles in which each cycle includes four components, namely planning action, acting, observing, and reflecting. The conclusion of the study is the ability to learn early counting in the group B at TK Bhakti Masyarakat Pagerharjo Wedarijaksa Pati before the research is still low. This is showed by the ability of the early counting that belongs to the category of Very Good Developing (BSB) and teh category of Developing As Expected (BSH) is only 35% and after he action with the pocket media, early counting ability increase to 95%.